Discourse Markers In The Essay Produced By EFL Students Of Mandalika University Of Education - Kamarudin (Cordova Journal : languages and culture studies, 2022)
The aim of this research was to investigate the types of discourse markers, and to elaborate on the types of discourse markers, and identify the reason why they used these types of discourse markers in the essay text. It used descriptive qualitative research. The subjects were the sixth-semester students of the English Language Department of Mandalika University of Education consisting of 19 students that were chosen out randomly. The data were in the form of the student’s essay writing text that was analyzed by using Fraser Taxonomy (1999). The result reveals that out of 8 types of discourse markers, there were 7 types that occurred in the essay text written by students.